2020
DOI: 10.4103/gmit.gmit_103_19
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of autocross-linked hyaluronic acid gel and intrauterine device for preventing intrauterine adhesions in infertile patients: A randomized clinical trial

Abstract: Objectives: The objective of this study is to evaluate the efficacy of autocross-linked hyaluronic acid (HA) compared with intrauterine device (IUD) for preventing intrauterine adhesions (IUAs) in infertile patients after hysteroscopic adhesiolysis. Materials and Methods: A randomized clinical trial (ChiCTR-IOR-16007746). Upon completion of adhesiolysis, 3 ml of HA gel was placed into the uterine cavity in Group A; 3 ml of HA gel and an IUD were placed in Group B; and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…25,26 However, combining an IUD with subsequent hormone therapy has shown unsatisfactory efficacy in several clinical trials. 14,27,28 Our data also showed that patients in group B had poorer postoperative AFS scores and menstruation conditions. Thus, exploring more effective treatments to improve clinical outcomes after hysteroscopic adhesiolysis is still needed.…”
Section: Discussionsupporting
confidence: 68%
“…25,26 However, combining an IUD with subsequent hormone therapy has shown unsatisfactory efficacy in several clinical trials. 14,27,28 Our data also showed that patients in group B had poorer postoperative AFS scores and menstruation conditions. Thus, exploring more effective treatments to improve clinical outcomes after hysteroscopic adhesiolysis is still needed.…”
Section: Discussionsupporting
confidence: 68%
“…The exact prevalence or real incidence of IUA is unknown, and may be underestimated, partly because of a lack of symptoms or the presence of vague symptoms, and partly because of neglect leading to the disease not being discovered even in those patients with clear symptoms [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ]; as well as partly because of the uncertain predisposing and causal factors [ 30 , 35 ]. Additionally, IUA varies with geographic location, study population, and the availability of investigations for diagnosis [ 29 , 36 ].…”
Section: Etiology and Prevalence Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
“…Many strategies or principles for decreasing the risk of developing IUA, such as the reduced use of electrosurgery and the minimization of trauma to the healthy endometrium and myometrium, have been proposed [ 73 , 74 , 75 , 76 , 77 , 78 , 79 ]. Additionally, many biomaterial agents, barrier methods, and cell or bio-agent therapies have been applied [ 14 , 16 , 24 , 27 , 28 , 29 , 30 , 31 , 35 , 37 , 40 , 43 , 44 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 ]. Figure 3 shows the recent development of agents available for the primary prevention of IUA after uterine surgery.…”
Section: Primary Prevention Of Intrauterine Adhesion (Iua)mentioning
confidence: 99%
See 2 more Smart Citations